IMMUNOGLOBULINS AND ALPHA-1-PROTEINASE INHIBITOR IN HUMAN INTERVERTEBRAL DISC MATERIAL - GUNER, A; OKTAY, G; KERMAN, M; GUNER, G (Portland Press, 1995)
[Abstract Not Available]
653rd Meeting of the Biochemical-Society-of-London -- SEP 13-16, 1994 -- UNIV SUSSEX, BRIGHTON, ENGLAND
Keywords: Ligamentum-Flavum; Proteoglycans